Transcriptome profiling of peanut gynophores revealed global reprogramming of gene expression during early pod development in darkness - Xia, Han (BioMed Central, 2013)
BACKGROUND: After the zygote divides few times, the development of peanut pre-globular embryo and fruit is arrested under white or red light. Embryo development could be resumed in dark condition after gynophore is buried in soil. It is interesting to study the mechanisms of gynophore development and pod formation in peanut. RESULTS: In this study, transcriptome analysis of peanut gynophore was performed using Illumina HiSeq™ 2000 to understand the mechanisms of geocarpy. More than 13 million short sequences were assembled into 72527 unigenes with average size of 394 bp. A large number of genes that were not identified previously in peanut EST projects were identified in this study, including most genes involved in plant circadian rhythm, intra-cellular transportation, plant spliceosome, eukaryotes basal transcription factors, genes encoding ribosomal proteins, brassinosteriod biosynthesis, light-harvesting chlorophyll protein complex, phenylpropanoid biosynthesis and TCA cycle. RNA-seq based gene expression profiling results showed that before and after gynophore soil penetration, the transcriptional level of a large number of genes changed significantly. Genes encoding key enzymes for hormone metabolism, signaling, photosynthesis, light signaling, cell division and growth, carbon and nitrogen metabolism as well as genes involved in stress responses were high lighted. CONCLUSIONS: Transcriptome analysis of peanut gynophore generated a large number of unigenes which provide useful information for gene cloning and expression study. Digital gene expression study suggested that gynophores experience global changes and reprogram from light to dark grown condition to resume embryo and fruit development.